Planning of Guidance and Counseling Service Programs to Improve the Achievement of Student Development Tasks in State Senior High School 1 Kinali - Elvina Elvina; Fuaddillah Putra; Citra Imelda Usman (Jurnal Counseling Care, 2024)
This research is motivated by students who lack independence in following the learning process, limited interaction during face-to-face learning, and some students who have difficulty accepting their own physical condition. The objectives of this study are to describe 1) The achievement of student development tasks at State Senior High School 1 Kinali, and 2) The planning of guidance and counseling programs to enhance the achievement of student development tasks at State Senior High School 1 Kinali. This research was conducted using a research and development method with a population of 302 students, and the sample consisted of 31 students from class XI Phase F 9. The instrument used was the Inventory of Developmental Tasks. Data analysis was performed using Developmental Task Analysis Software. The research results are as follows: 1) The achievement of student developmental tasks (Study in class XI Phase F 9) is generally in the category of self-awareness development level. 2) The planning of guidance and counseling programs to enhance the achievement of student developmental tasks at State Senior High School 1 Kinali includes services such as information services, group counseling services, collaborative services, and bibliotherapy services. Based on the results of the research, recommendations can be made for students to identify unfulfilled developmental tasks and use this research as a guide for improvement.